Determination of permeability, plasma protein binding, blood partitioning, pharmacokinetics and tissue distribution of Withanolide A in rats: A neuroprotective steroidal lactone. Issue 7 (4th October 2018) - Singh, Sandeep K.; Valicherla, Guru R.; Joshi, Pankaj; Shahi, Sudhir; Syed, Anees A.; Gupta, Anand P.; Hossain, Zakir; Italiya, Kishan; Makadia, Vishal; Singh, Shio K.; Wahajuddin, Mohammad; Gayen, Jiaur R.
Abstract: Preclinical Research & Development Withanolide A (WA), a steroidal lactone is a major bioactive constituent of Withania somnifera (L.) with remarkable neuropharmacological activity. In this study, we investigated the permeability, plasma protein binding (PPB), blood partitioning, intravenous (i.v.), and oral pharmacokinetics as well as i.v. tissue distribution (TD) of pure WA in a rat model. The PPB, RBCs partitioning, and permeability of WA were determined by Ultra Performance Liquid Chromatography (UPLC) method. However, the pharmacokinetics and TD of WA were evaluated by validated and sensitive liquid chromatography coupled mass spectrometry (LC‐ESI‐MS/MS) method. The PPB and permeability of WA were determined by equilibrium dialysis and parallel artificial membrane permeability assay method, respectively. The results demonstrated that WA has high PPB and passive permeability. Furthermore, WA was found to have fast equilibration between RBCs and plasma. Following i.v. (2 mg/kg) and per‐oral (25 mg/kg) administration of WA, the max concentration (Cmax ) in plasma was found as 85.53 ± 6.54 and 48.04 ±5.78 ng/mL, respectively. The TD study results indicated that WA has a rapid and wide TD. The maximum concentration in various tissues was found in following order: Clung > Cliver > Ckidney ≈ Cspleen > Cheart > Cbrain . The preclinical in vitro, as well as pharmacokinetics and TD results, are anticipated to support the future preclinical and clinical application of WA.